2020
DOI: 10.1111/1440-1681.13388
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Treg cells from patients with cerebral aneurysms displayed deficiency in ICOS expression and function

Abstract: Inducible costimulator (ICOS) is a member of the CD28 family. When activated, ICOS signalling promotes FOXP3 CNS2 gene demethylation and stabilizes Treg differentiation. Cerebral aneurysm (CA) is the local ballooning of the cerebral vasculature, characterized by higher levels of inflammation mediators and tissue remodelling. FOXP3+ Treg cell dysfunction may contribute to CA pathogenesis. In this study, the expression and function of ICOS in Treg cells was investigated. Circulating CD4+CD25hi T cells from CA su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…In this study, the imbalance of CD4 + T cell subsets in IA patients was further confirmed, with higher frequencies of C02 (CD27 + CD4 + Tem), C03(HLA-DR + CD4 + Tn), C05(CD27 - CD4 + Tem), and C17 (HLA-DR + CD4 + Tcm), and lower frequencies of C09(HLA-DR - CD4 + Tn), C11(Treg cells), C26(CXCR5 + CD4 + Tem), and C27(HLA-DR - CD4 + Tcm). In addition, recent studies have shown that Treg cells were significantly decreased in IA patients compared with HCs ( 9 , 20 22 ) Additionally, the expression leves of Foxp3, and IL-10 were significantly lower in Treg cells from IA patients than from HCs ( 20 22 ), which is also consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, the imbalance of CD4 + T cell subsets in IA patients was further confirmed, with higher frequencies of C02 (CD27 + CD4 + Tem), C03(HLA-DR + CD4 + Tn), C05(CD27 - CD4 + Tem), and C17 (HLA-DR + CD4 + Tcm), and lower frequencies of C09(HLA-DR - CD4 + Tn), C11(Treg cells), C26(CXCR5 + CD4 + Tem), and C27(HLA-DR - CD4 + Tcm). In addition, recent studies have shown that Treg cells were significantly decreased in IA patients compared with HCs ( 9 , 20 22 ) Additionally, the expression leves of Foxp3, and IL-10 were significantly lower in Treg cells from IA patients than from HCs ( 20 22 ), which is also consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Dysregulation of CD4 + T cells is involved in the pathogenesis of various chronic inflammatory disorders. A previous study demonstrated that IA patients exhibited an imbalance of CD4 + T cell subsets ( 11 , 18 20 ). Zhang et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation